2017
DOI: 10.1590/1982-021620171949616
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of parents regarding newborn screening test, after accessing the website “Babies’ Portal” - Heel prick test

Abstract: Purpose: to assess the knowledge of mothers about the heel prick test, develop contents on this test to make it available on the "Babies' Portal" website, evaluate and validate the informative material developed. Methods: this study was conducted in three stages, that is, the first stage which is about a descriptive study involving 105 mothers of newborn children before performing the neonatal screening "Heel Prick Test", the second one consisting in the development of the website "Babies' Portal", and the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
4
0
2
Order By: Relevance
“…However, the mothers require focused education specifically regarding (a) genetic and congenital conditions screened by HPST, (b) timing of the results release and the need for follow up, (c) the meaning of the abnormal findings, and (d) the storage of the dried blood spots for future research purposes. Our findings about the specific areas of knowledge inadequacy strongly resonated with the research findings of other studies that identified similar areas of knowledge inadequacy and misconceptions regarding the HPST (Arduini et al 2017 ; Fitzpatrick et al 2019 ; Franková et al 2019 ; Mendes et al 2017 ; Rosales et al 2015 ; Silva et al 2017 ; Twfeeq and Abed 2016 ). Collectively, the results of these research studies, when added to our findings, should be utilized by healthcare providers, and be integrated into the primary health care practices, in order to improve the information provided to mothers of newborns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the mothers require focused education specifically regarding (a) genetic and congenital conditions screened by HPST, (b) timing of the results release and the need for follow up, (c) the meaning of the abnormal findings, and (d) the storage of the dried blood spots for future research purposes. Our findings about the specific areas of knowledge inadequacy strongly resonated with the research findings of other studies that identified similar areas of knowledge inadequacy and misconceptions regarding the HPST (Arduini et al 2017 ; Fitzpatrick et al 2019 ; Franková et al 2019 ; Mendes et al 2017 ; Rosales et al 2015 ; Silva et al 2017 ; Twfeeq and Abed 2016 ). Collectively, the results of these research studies, when added to our findings, should be utilized by healthcare providers, and be integrated into the primary health care practices, in order to improve the information provided to mothers of newborns.…”
Section: Discussionsupporting
confidence: 88%
“…In order to optimize the health promotion outcomes of the HPST and design structured health education interventions, healthcare providers need to bridge the gaps in knowledge, perceptions, and unique needs exhibited by mothers. Well-designed HPST education programs demonstrate promising results of increased knowledge and awareness and maximize uptake of NS among mothers (Mendes et al 2017 ; Tariq et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…All mothers of patients diagnosed with phenylketonuria (n = 14) performed prenatal care, but this fact does not guarantee that mothers were informed in prenatal about the importance of the foot test for their babies, being hospital discharge postpartum without without the foot test. Mendes et al (2017) states that misinformation negatively influences the early diagnosis of the disease as well as the initiation of treatment in a timely manner.…”
Section: Resultsmentioning
confidence: 99%
“…for the care of sickle cell disease and other hemoglobinopathies in SUS, as recommended by Ordinance MO 1.391/05, aiming at promoting a change in the natural history of sickle cell disease in Brazil, reducing the rate of morbidity and mortality, promoting longevity with quality of life for people with this disease, guiding those with sickle cell trait and informing the general population (22) . Sickle cell trait is associated with the risk of birth of future children with the disease; therefore, knowing the epidemiological profile with regard to hemoglobinopathies in the Brazilian population is important to establish the health care network and provide genetic counseling to patients and their families (12) .…”
Section: Discussionmentioning
confidence: 99%